Significance of peripheral mononuclear cells producing interferon-γ in response to insulin B:9-23-related peptides in subtypes of type 1 diabetes - Oikawa, Yoichi (Clinical immunology (Orlando, Fla.), 2019)
Copyright © 2019 Elsevier Inc. All rights reserved.